G protein-coupled receptors related to autoimmunity in postural orthostatic tachycardia syndrome - Yoko Sunami; Keizo Sugaya; Kazushi Takahashi (Immunological Medicine)
Postural orthostatic tachycardia syndrome (POTS) is characterized by exaggerated orthostatic tachycardia in the absence of orthostatic hypotension. The pathophysiology of POTS may involve hypovolemia, autonomic neuropathy, a hyperadrenergic state, and cardiovascular deconditioning, any of which can co-occur in the same patient. Furthermore, there is growing evidence of the role of autoimmunity in a subset of POTS cases. In recent years, investigators have described an increased rate of autoimmune comorbidities as evidenced by the finding of several types of neural receptor autoantibody and non-specific autoimmune marker in patients with POTS. In particular, the association of the disease with several types of anti-G protein-coupled receptor (GPCR) antibodies and POTS has frequently been noted. A previous study reported that autoantibodies to muscarinic AChRs may play an important role in POTS with persistent, gastrointestinal symptoms. To date, POTS is recognized as one of the sequelae of coronavirus disease 2019 (COVID-19) and its frequency and pathogenesis are still largely unknown. Multiple autoantibody types occur in COVID-related, autonomic disorders, suggesting the presence of autoimmune pathology in these disorders. Herein, we review the association of anti-GPCR autoantibodies with disorders of the autonomic nervous system, in particular POTS, and provide a new perspective for understanding POTS-related autoimmunity.